2008
DOI: 10.1080/13607860801951820
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on depressive symptoms by age and gender in African American twins

Abstract: Depression is typically considered relative to individuals and thought to originate from both biological and environmental factors. However, the environmental constraints and insults that African Americans experience likely influence the concordance by age and gender for depression scores among adult African American twins. Monozygotic (MZ) (n = 102) and Dizygotic (DZ) (n = 110) twins, age 25-88 years in the Carolina African American Twin Study of Aging were examined using an 11-item version of the CES-D measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Extending genetic association studies to more diverse racial/ethnic populations – especially of women – is therefore needed. These studies are likely to be informative, as depression appears at least as heritable (around 40%) among African Americans 22,23 and Hispanics 24 compared to European Americans 1 . Such extensions are also important given known racial/ethnic (as well as sex) disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Extending genetic association studies to more diverse racial/ethnic populations – especially of women – is therefore needed. These studies are likely to be informative, as depression appears at least as heritable (around 40%) among African Americans 22,23 and Hispanics 24 compared to European Americans 1 . Such extensions are also important given known racial/ethnic (as well as sex) disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a longitudinal study of 187 twin pairs initially aged 59–70, Carmelli et al (2000) reported that the heritability of a quantitative index of depression symptomatology increased from 25 % at baseline to 55 % at 10-year follow-up. Alternatively, rather than an increase in heritability with age, Whitfield et al (2008) reported that the heritability of liability to a categorical indicator of depression decreased from 28 % for twins 49 years and younger to 6 % for twins 50 years and older in a sample of 212 twin pairs. Finally, Neiss and Almeida (2004) reported evidence of both increases and decreases in heritable influences on different measures of psychological distress from a single sample of 210 pairs of twins age 25–74 years from the National Survey of Midlife in the United States Survey (MIDUS).…”
Section: Introductionmentioning
confidence: 99%
“…There were 12 studies in which AA representation exceeded 10% of the sample – including two studies focusing exclusively on AA (Chapman et al, 2012; Whitfield et al, 2008) (Table 2). Ten of the 12 studies shown in Table 2, had AA proportions ranging from 11% to 24% of their samples.…”
Section: Resultsmentioning
confidence: 99%
“…The second study focusing exclusively on AA was a twin study on the heritability of depressive symptoms as measured by the Center for Epidemiologic Studies-Depression Scale (CES-D), using a sample of 212 twins (Whitfield et al, 2008). The study used cutoff points to dichotomize the CES-D scores into “depressed” vs. “non-depressed” to obtain heritability estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation